Plant Allergen-Induced Contact Dermatitis - Esser, Philipp R.; Mueller, Sabine; Martin, Stefan F. (Planta Medica, 2019)
Although manifold beneficial effects of plant compounds for the treatment of skin disorders are known, cutaneous exposure to plants can also result in various types of incompatibility reactions such as contact dermatitis. In this mini-review, we briefly describe the different clinical forms of contact dermatitis (photoinduced, irritative, and allergic form) and highlight recent publications in the field of contact dermatitis. Major topics are recent recommendations regarding testing for plant contact dermatitis, advances in understanding the immunological mechanisms of plant contact dermatitis, and case reports for plant contact dermatitis. Unfortunately, most people still associate the terms “healthy and safe to use” with plant compounds due to their natural origin, leading to an increased utilization, be it for home-made remedies or as cosmetics. Therefore, it is on the one hand important to raise awareness in a broad audience that plants may cause contact dermatitis and on the other hand to indicate to clinicians that plants should be included in a patch test if a history of plant exposure exists.
Keywords: allergy; contact dermatitis; plant-induced contact dermatitis; case report; mechanism; review